Lone survivor [compact disc, unabridged] : the eyewitness account of Operation Redwing and the lost heroes of SEAL Team 10 - Luttrell, Marcus (Hachette Audio, 2013)
Four US Navy SEALS departed one clear night in early July, 2005 for the mountainous Afghanistan-Pakistan border for a reconnaissance mission. Five days later, only one of those Navy SEALS made it out alive. This is the story of the only survivor of Operation Redwing, SEAL team leader Marcus Luttrell, and the extraordinary firefight that led to the largest loss of life in American Navy SEAL history.